Collective Renewable Energy Prosumers and the Promises of the Energy Union: Taking Stock - Horstink, Lanka (2020)
A key strategy in the European Union’s ambition to establish an ‘Energy Union’ that is not just clean, but also fair, consists of empowering citizens to actively interact with the energy market as self-consumers or prosumers. Although renewable energy sources (RES) prosumerism has been growing for at least a decade, two new EU directives are intended to legitimise and facilitate its expansion. However, little is known about the full range of prosumers against which to measure policy e ectiveness. We carried out a documentary study and an online survey in nine EU countries to shed light on the demographics, use of technology, organisation, financing, and motivation as well as perceived hindering and facilitating factors for collective prosumers. We identified several internal and external obstacles to the successful mainstreaming of RES prosumerism, among them a mismatch of policies with the needs of di erent RES prosumer types, potential organisational weaknesses as well as slow progress in essential reforms such as decentralising energy infrastructures. Our baseline results o er recommendations for the transposition of EU directives into national legislations and suggest avenues for future research in the fields of social, governance, policy, technology, and business models.